Modulation of autophagy by an innovative phytocosmetic preparation (Myrothamnus flabelifolia and Coffea arabica) in human fibroblasts and its effects in a clinical randomized placebo-controlled trial - Biscaro, Rafael C.; Mussi, Lilian; Sufi, Bianca; Padovani, Giovana; Camargo Junior, Flavio B.; Magalhães, Wagner V.; Di Stasi, Luiz C. [UNESP] (Wiley, 2022)
Background: Autophagy is a natural and evolutionary mechanism that reduces cell toxic components and reutilizes metabolites to provide energy and renew cell function, which is linked to a wide range of age-related diseases, including those that affect the skin. Positive modulation of autophagy is useful to treat skin disorders and new active herbal products are potential candidates as autophagy modulators. Aims: The present study aimed to evaluate the effects of a phytocosmetic formulation containing Myrothamnus flabellifolia leaf and Coffea arabica seed plant extracts (MflCas) on the ubiquitin-proteasome and autophagy markers in human dermal fibroblasts, and investigate its topical skin effects in a randomized, simple-blind, and placebo-controlled trial. Methods: Human dermal fibroblasts were used to determine proteasome activity, protein carbonylation, LC3B protein, and lipofuscin production by luminescence and immune-enzymatic assays, and to determinate gene expression of autophagy biomarkers (Atg5, Atg7, EI24, EIF2A, Park2, foxo1, and mTOR) by RT-PCR. A clinical trial was conducted to evaluate the effects of MflCas on the hand, face, and forearms skin features after treatment by 56 days. Results: Topical treatment with MflCas improved several skin features of volunteers, mainly skin aging and pigmentation signals. On the hand skin, MflCas 2% after 56 days of treatment, reduced the spots length (30.8%), skin contrast (42.2%), and increased skin homogeneity (63.2%) and skin lightening effect (1.4%). On the face skin, topical treatment after 56 days reduced the spots length (21.5%), wrinkles area (8.1%), and wrinkles volume (5.6%) with an increment in face skin homogeneity (59.5%). These effects were related to the ability of MflCas to reduce proteasome activity protein carbonylation, and lipofuscin level, increase LC3B production, downregulate Atg7 and mTOR genes, and upregulate Park2 gene expressions. Conclusions: The phytocosmetic preparation containing Myrothamnus flabellifolia leaf and Coffea arabica seed modulated ubiquitin-proteasome and autophagy process, representing an innovative and safe herbal preparation to improve skin features, mainly acting as skin anti-aging and lightening agent.
Keywords: autophagy; coffee; resurrection plant; skin aging; skin pigmentation; ubiquitin-proteasome system